Production Pattern of Ajmalicine in Catharanthus roseus (L.) G. Don. Cell Aggregates Culture in the Airlift Bioreactor - ESYANTI, RIZKITA RACHMI; MUSPIAH, AIDA (HAYATI Journal of Biosciences, 2009)
A research has been conducted to optimize the rate of aeration and initial weight of cell aggregates in the production of ajmalicine in Catharanthus roseus cell culture in airlift bioreactor. Catharanthus roseus culture were grown in Zenk medium with the addition of 2.50 x 10-6 M naphthalene acetic acid (NAA) and 10-5 M benzyl amino purine (BAP). Cell aggregates were sub-cultured two times before transferring 20 and 30 g/fw of cell aggregates into bioreactor, respectively, and aerated with the rate of 0.25 l min-1 and 0.34 l min-1, respectively. The pattern of ajmalicine production in bioreactor were observed in every three days within 24 days. Qualitative and quantitative analysis were conducted using HPLC connected to Cromatopac CL-7A Plus. The results showed that the cell aggregates and medium contain ajmalicine. The highest concentration was obtained in combination of 30 g/fw and 0.34 l min-1 aeration compare to 20 g/fw - 0.25 l min-1, 20 g/fw - 0.34 l min-1, as well as 30 g/fw – 0.25 l min-1/sup>. The highest ajmalicine content in cell aggregates was obtained on the 12 days (79.23 µg g-) whilst in medium was obtained in the 18thsup> days (981.15 µg l-). Key words: ajmalicine, cell aggregates culture, C. roseus, airlift bioreactor